A planetary boundary-based method for freshwater use in life cycle assessment: Development and application to a tomato production case study. (March 2020) - Bjørn, Anders; Sim, Sarah; Boulay, Anne-Marie; King, Henry; Clavreul, Julie; Lam, Wan Yee; Barbarossa, Valerio; Bulle, Cécile; Margni, Manuele
Highlights: Method translates water consumption to area-equivalent of mean monthly flow. This is compared to an assigned share of "safe operating space" at watershed-level. Method is demonstrated on case study for two illustrative sharing principles. Work contributes to improving planetary boundaries-based life cycle assessments. Abstract: Existing methods for applying the planetary boundary concept in life cycle assessment are not sufficiently spatially and temporally resolved. Here, we develop a new method for freshwater use based on the safe operating space (SOS) at watershed-level. The SOS is based on the concept of environmental flow requirements, which is the share of mean monthly flow that should be reserved to achieve or maintain "fair conditions" of aquatic ecosystems. The method is composed of two steps. First, water consumption is multiplied by a characterization factor, which converts it to an environmental impact, expressed as an area-equivalent of a watershed's mean monthly flow. Second, the environmental impact is compared to an assigned share of SOS to determine if the activity causing it can be considered environmentally sustainable, with respect to a chosen principle for sharing the SOS. The method is demonstrated for a case study on water consumed for irrigation in open-field tomato production in 27 watersheds, spanning 10 countries and 5 continents, based on data for 316 farms in the year 2014. Water consumption was modelled from crop characteristics, climatic data and the assumed type of irrigation system. Two principles, "status quo" and "gross value added", were illustratively applied for the assignment of SOS to 1 tonne of tomatoes. The characterization factors developed span two orders of magnitude from 10th to 90th percentile, which shows the relevance of a spatially and temporally explicit assessment. In the case study, the characterization factors largely determine the high variability in the resulting environmental impacts between watersheds, which ranged from 400 m 2 to 50, 000 m 2 per tonne of tomatoes. The analysis would suggest that the freshwater use by current tomato farming is environmentally sustainable in all months in a maximum of 2 of the 27 watersheds with respect to the two principles applied for sharing the SOS. The method can be used as a basis to identify potential "planetary boundary hotspots" in the life cycle of products and to inform appropriate interventions. Two key challenges are the lack of appropriate spatial and temporal data in current life cycle inventories and the choice of sharing principle for assigning the SOS.